Paracetamol vs. Ibuprofen in Preterm Infants With Hemodynamically Significant Patent Ductus Arteriosus: A Non-inferiority Randomized Clinical Trial Protocol - García-Robles, Ana; Gimeno Navarro, Ana; Serrano Martín, María del Mar; Párraga Quiles, María José; Parra Llorca, Anna; Poveda-Andrés, José Luis; Vento Torres, Máximo; Aguar Carrascosa, Marta (Frontiers in Pediatrics, 2020)
Background: Currently, the first line treatment of persistent ductus arteriosus (PDA) is either indomethacin or ibuprofen. However, the potentially life-threatening side effects associated to their use have prompted physicians to look for alternative options. The incorporation of paracetamol as an alternative to ibuprofen in the management of PDA is still based on insufficient clinical evidence. Hence, more clinical trials are needed to establish a therapeutic role for paracetamol in the management of PDA that take into consideration short- and long-term safety and efficacy outcomes. Study Design This is a non-inferiority, randomized, multicenter, double-blinded study to evaluate the efficacy and safety of intravenous (IV) paracetamol versus IV ibuprofen (standard treatment) for PDA in preterm patients with a gestational age ≤30 weeks. At baseline, patients will be randomized (1:1) to treatment with paracetamol or ibuprofen. The primary endpoint is closure of the ductus after the first treatment course. Secondary endpoints are related to effectiveness (need for a second treatment course, rescue treatment, reopening rate, time to definitive closure, need for surgical ligation), safety (early and long-term complications), pharmacokinetics and pharmacodynamics, pharmacogenetics, pharmacoeconomics and genotoxicity. Discussion In the present trial, we will employ paracetamol as treatment of PDA in patients who are candidates for pharmacological closure of the ductus. If the non-inferiority hypothesis is demonstrated, paracetamol will emerge as the drug of choice for the treatment of PDA in preterm infants due to its lower cost and more favorable side effect profile. In addition, our study aims to unravel factors that influence closure response, allowing for an individualized and more efficient therapeutic approach. Trial registration: ClinicalTrials.gov Identifier: NCT04037514. EudraCT: 2015-003177-14